Brexit as heredity redux: Imperialism, biomedicine and the NHS in Britain. Issue 6 (November 2020) - Fitzgerald, Des; Hinterberger, Amy; Narayan, John; Williams, Ros
What is the relationship between Brexit and biomedicine? Here we investigate the Vote Leave official campaign slogan 'We send the EU £350 million a week. Let's fund our NHS instead' in order to shed new light on the nationalist stakes of Brexit. We argue that the Brexit referendum campaign must be situated within biomedical policy and practice in Britain. We propose a re-thinking of Brexit through a cultural politics of heredity to capture how biomedicine is structured around genetic understandings of ancestry and health, along with the forms of racial inheritance that structure the state and its welfare system. We explore this in three domains: the NHS and health tourism, data sharing policies between the NHS and the Home Office, and the NHS as an imperially resourced public service. Looking beyond the Brexit referendum campaign, we argue for renewed sociological attention to the relationships between racism, biology, health and inheritance in British society.